1993
DOI: 10.1523/jneurosci.13-06-02601.1993
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 induces substance P in sympathetic ganglia through the induction of leukemia inhibitory factor (LIF)

Abstract: It has become increasingly clear that immune cytokines perform growth and differentiation functions in the nervous system similar to those performed in the immune system. In previous studies we have shown that interleukin-1 beta (IL-1 beta) raises substance P (SP) and the mRNA coding for its preprotachykinin precursor in cultured sympathetic superior cervical ganglia (SCG) (Jonakait and Schotland, 1990; Hart et al., 1991a). The action of IL-1 is blocked both by depolarization of the ganglia and by glucocortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
78
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 54 publications
4
78
1
Order By: Relevance
“…A recent study has found that IL-1␤ may regulate leukemia inhibitory factor (LIF) release from ganglion nonneuronal cells, that treatment of pure neuronal cultures with LIF induces SP expression, and that cocultures with LIF antibody prevent the SP increase caused by nonneuronal cells (31,45). These studies provide further support for LIF as a signaling molecule regulating SP expression in airway ganglia.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent study has found that IL-1␤ may regulate leukemia inhibitory factor (LIF) release from ganglion nonneuronal cells, that treatment of pure neuronal cultures with LIF induces SP expression, and that cocultures with LIF antibody prevent the SP increase caused by nonneuronal cells (31,45). These studies provide further support for LIF as a signaling molecule regulating SP expression in airway ganglia.…”
Section: Discussionmentioning
confidence: 88%
“…airway inflammation; airway smooth muscle contraction; muscarinic agonists; neurokinin receptor; airway innervation INTERLEUKIN-1 (IL-1), an inflammatory cytokine, has been reported to increase substance P (SP) release and gene expression in neurons of sensory and sympathetic ganglia (27,31,45). The IL-1␤ level in bronchoalveolar lavage fluid is increased in asthmatic patients (6,7), and IL-1␤ induces airway hyperresponsiveness (AHR) in rats (50) and isolated human bronchi (4,23).…”
mentioning
confidence: 99%
“…IL-1p regulates substance P levels in sympathic ganglion cells (Hart et al, 1991) through the induction of a neuropoietic cytokine leukaemia inhibitory factor (LIF) (Shadiack et al, 1993). IL-P could alter neuropeptide expression in primary sensory neurones secondary to an increase in NGF levels since NGF has well known actions on the regulation of both substance P and CGRP in adult DRG neurones (Lindsay & Harmar, 1989;Woolf et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that SP is up-regulated in DRG neurons in CFA-inflamed rats [12], and that the concentration of SP increases in the serum of patients with long-standing rheumatoid arthritis [18]. In contrast, there has been no direct evidence that SP is upregulated in the lumbar SG of inflamed animals and transported and released from sympathetic terminals [19]. Our present observation is, to our knowledge, the first to show an increased expression of SP in SG as a result of inflammation.…”
Section: Discussion (1) Sp Was Involved In the Bf Increase Response Tmentioning
confidence: 99%
“…Our present observation is, to our knowledge, the first to show an increased expression of SP in SG as a result of inflammation. An inflammatory cytokine, IL-1, is reported to stimulate the up-regulation of SP through the induction of a leukemia inhibitory factor in SG [19]. The effect of immunocytokines on SP expression has been studied in relation to nerve injury [20], and it is possible that IL-1 is also increased in SG with peripheral inflammation.…”
Section: Discussion (1) Sp Was Involved In the Bf Increase Response Tmentioning
confidence: 99%